Metastatic Cervix Uterine Cancer and Therapeutics Updates: A Case Report and Literature Review - Pereira, Luís Gustavo Ramos Raupp; Comarú, Luísa Motter; Guzzon, Micael; Silva, Eduarda Alberti Lopes; Rabuske, Júlhia Spuldaro; Negrão, Larissa Roberta; Copatti, Raíssa dos Santos; Reichert, Paulo Roberto (Brazilian Journal of Oncology, 2025)
Metastatic cervical cancer presents new measures related to the association of biological therapies with conventional treatment that varies according to the presence of biomarkers. Based on a case report, we reviewed therapeutic modalities and updates on the use of concomitant immunobiological and oncological treatments to combat invasive cervical cancer. The use of pembrolizumab is a new option in patients with positive PD-L1 associated with metastatic cervical cancer, having demonstrated a favorable toxicity profile and improved survival. In this case report, we describe a 52-year-old woman diagnosed with metastatic cervical cancer who underwent to chemotherapy (CT) with paclitaxel and carboplatin, as well as immunotherapy with pembrolizumab for PD-L1 positive cervical neoplasm and metastasectomy of hepatic lesions. The patient remains under outpatient care with no signs of active disease.
Keywords: uterine cervical neoplasms; neoplasm metastasis; immunotherapy; neoplasm staging; metastasectomy